2016
DOI: 10.1002/ijc.30221
|View full text |Cite
|
Sign up to set email alerts
|

Kif14 overexpression accelerates murine retinoblastoma development

Abstract: The mitotic kinesin KIF14 has an essential role in the recruitment of proteins required for the final stages of cytokinesis. Genomic gain and/or overexpression of KIF14 has been documented in retinoblastoma and a number of other cancers, such as breast, lung and ovarian carcinomas, strongly suggesting its role as an oncogene. Despite evidence of oncogenic properties in vitro and in xenografts, Kif14’s role in tumor progression has not previously been studied in a transgenic cancer model. Using a novel Kif14 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…7,14 In vivo model also demonstrated upregulation of KIF14 resulted in increased tumor growth rate and accelerated tumor initiation. 12 This study demonstrated the increased mRNA abundance of KIF14 in MB. This finding was also in line with previous study showing a profound upregulation of KIF14 in MB compared with fetal brain.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…7,14 In vivo model also demonstrated upregulation of KIF14 resulted in increased tumor growth rate and accelerated tumor initiation. 12 This study demonstrated the increased mRNA abundance of KIF14 in MB. This finding was also in line with previous study showing a profound upregulation of KIF14 in MB compared with fetal brain.…”
Section: Discussionmentioning
confidence: 53%
“…10,11 It has been shown that KIF14 overexpression accelerated initiation of tumor formation. 12 In contrast, siRNA-induced silencing KIF14 resulted in tumor growth inhibition and cell cycle arrest in hepatocellular carcinoma and glioma. 13,14 In the present study, we demonstrated increased KIF14 mRNA and protein abundance in MB samples.…”
mentioning
confidence: 98%
“…Retinoblastoma was among the first tumors where KIF14 overexpression was noted [56] , and KIF14 overexpression was found to accelerate retinoblastoma tumorigenesis in a murine model [57] . KIF14 overexpression has also been found in both ovarian and chemo-resistant breast cancers, where KIF14 inhibition leads to chemo-sensitization [58, 59] .…”
Section: Kif14 Is Mutated In Primary Microcephaly and Upregulated mentioning
confidence: 99%
“…More recently, using a commercially available small‐animal OCT system, we showed that this technique can detect the earliest signs of tumors in the TAg‐RB model, corresponding to their first appearance by histology (Figure g) (Wenzel, O’Hare, Shadmand, & Corson, ), and we used this finding to show that overexpression of the oncogene Kif14 accelerates not just tumor growth but also tumor initiation in this model (O’Hare et al, ).…”
Section: Imaging Retinoblastomamentioning
confidence: 85%